A red herring without mustard - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2011)
Flavia's discovery of an old Gypsy woman who's been attacked in her wagon sends the girl off on an investigation that will reveal more of Buckshaw's secrets as well as new information about Harriet, the mother Flavia never knew.